2019
DOI: 10.48550/arxiv.1904.11155
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A survey of recent developments on Hessenberg varieties

Abstract: This article surveys recent developments on Hessenberg varieties, emphasizing some of the rich connections of their cohomology and combinatorics. In particular, we will see how hyperplane arrangements, representations of symmetric groups, and Stanley's chromatic symmetric functions are related to the cohomology rings of Hessenberg varieties. We also include several other topics on Hessenberg varieties to cover recent developments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 72 publications
1
16
0
Order By: Relevance
“…, m 4 ) = (1, 0, 0, 2), then we have ℓ := h − m = (2, 5, 4, 5). Hence, the procedure is as follows: 3) , where ℓ (1) = (2, 5, 4, 5), ℓ (2) = (4, 3, 4),…”
Section: We Denote Positive Roots In φ +mentioning
confidence: 99%
See 2 more Smart Citations
“…, m 4 ) = (1, 0, 0, 2), then we have ℓ := h − m = (2, 5, 4, 5). Hence, the procedure is as follows: 3) , where ℓ (1) = (2, 5, 4, 5), ℓ (2) = (4, 3, 4),…”
Section: We Denote Positive Roots In φ +mentioning
confidence: 99%
“…, m ′ 4 ) = (1, 2, 0, 2), then we have ℓ ′ := h − m ′ = (2, 3, 4, 5). Hence, the procedure is as follows: 3) , where ℓ ′(1) = (2, 3, 4, 5), ℓ ′(2) = (2, 3, 4), ℓ ′(3) = (2, 3), and ℓ ′( 4) is not defined. The product v…”
Section: We Denote Positive Roots In φ +mentioning
confidence: 99%
See 1 more Smart Citation
“…Hessenberg varieties have been studied by applied mathematicians, combinatorialists, geometers, representation theorists, and topologists. See [AH19] for a survey of some recent developments. Our goal is to understand better the structure of these varieties, and in particular what restrictions on such structure exist.…”
Section: Introductionmentioning
confidence: 99%
“…This subject is relatively new, and it has been found that geometry, combinatorics, and representation theory interact nicely on Hessenberg varieties (cf. [2]). As one of the interactions, the cohomology ring of a regular nilpotent Hessenberg variety can be described in terms of the logarithmic derivation module of the ideal arrangement ( [4]).…”
Section: Introductionmentioning
confidence: 99%

Uniform bases for ideal arrangements

Enokizono,
Horiguchi,
Nagaoka
et al. 2019
Preprint
Self Cite